LncRNA‐01126 inhibits the migration of human periodontal ligament cells through MEK/ERK signaling pathway. (2nd April 2020) - Zhu, Yiting; Ai, Rongshuang; Ding, Zhiqiang; He, Qian; Zhang, Xinxin; Dong, Yilin; He, Yujuan
Abstract: Background and Objective: Accumulating findings revealed that long noncoding RNAs (lncRNAs) are crucial regulator molecules in the progression of periodontitis. This study aimed to investigate the biological roles and mechanisms of lncRNA‐01126 in the progression of periodontitis. Materials and Methods: RT‐qPCR was used to detect the levels of lncRNA‐01126 in gingival tissues and human periodontal ligament cells (hPDLCs). Cell transfection experiments were performed to knock down or overexpress the level of lncRNA‐01126 in hPDLCs. Cell Counting Kit‐8, wound‐healing assay, transwell assay, and flow cytometric analysis were used to evaluate the function of lncRNA‐01126 in the progression of periodontitis. Finally, the signaling pathway was assessed by western blot. Results: LncRNA microarray discovered that lncRNA‐01126 was the most significantly increased lncRNA in periodontitis patients. LncRNA‐01126 markedly increased in the gingival tissues of periodontitis mice and in the hPDLCs treated with lipopolysaccharide of Porphyromonas Gingivalis (LPS‐PG). Furthermore, in vitro experiments showed that lncRNA‐01126 dramatically suppressed the migration of hPDLCs through MEK/ERK signaling pathway. Conclusion: LncRNA‐01126 plays a crucial role in inhibiting the migration of hPDLCs through MEK/ERK signaling pathway.